1998
DOI: 10.1073/pnas.95.12.6619
|View full text |Cite
|
Sign up to set email alerts
|

Lignin monomer composition is determined by the expression of a cytochrome P450-dependent monooxygenase in Arabidopsis

Abstract: The phenylpropanoid pathway provides precursors for the biosynthesis of soluble secondary metabolites and lignin in plants. Ferulate-5-hydroxylase (F5H) catalyzes an irreversible hydroxylation step in this pathway that diverts ferulic acid away from guaiacyl lignin biosynthesis and toward sinapic acid and syringyl lignin. This fact led us to postulate that F5H was a potential regulatory step in the determination of lignin monomer composition. To test this hypothesis, we have used Arabidopsis to examine the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
267
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 299 publications
(293 citation statements)
references
References 30 publications
23
267
0
3
Order By: Relevance
“…Promoter fusion analysis suggested that corresponding AtCAD-D and -C genes may be expressed in xylem and fibers, although only fibers contain S lignin. The ability to reduce sinapaldehyde to sinapyl alcohol in xylem (a G unitenriched tissue) is consistent with the fact that sinapyl alcohol was synthesized in xylem bundles when ferulate-5-hydroxylase was overexpressed in transgenic Arabidopsis (Meyer et al, 1998;Sibout et al, 2002). These observations demonstrate that the absence of SAD-type protein in vessels of stems and roots likely would not be the limiting step for S-unit biosynthesis in these tissues, at least in Arabidopsis, and that other CADs could be involved in this processes.…”
Section: Atcad-d Is Involved In Biosynthesis Of G or S Lignin Precursmentioning
confidence: 53%
“…Promoter fusion analysis suggested that corresponding AtCAD-D and -C genes may be expressed in xylem and fibers, although only fibers contain S lignin. The ability to reduce sinapaldehyde to sinapyl alcohol in xylem (a G unitenriched tissue) is consistent with the fact that sinapyl alcohol was synthesized in xylem bundles when ferulate-5-hydroxylase was overexpressed in transgenic Arabidopsis (Meyer et al, 1998;Sibout et al, 2002). These observations demonstrate that the absence of SAD-type protein in vessels of stems and roots likely would not be the limiting step for S-unit biosynthesis in these tissues, at least in Arabidopsis, and that other CADs could be involved in this processes.…”
Section: Atcad-d Is Involved In Biosynthesis Of G or S Lignin Precursmentioning
confidence: 53%
“…Sewalt and R.A. Dixon, unpublished results). Recently, it was shown that modification of lignin composition by overexpression of F5H in transgenic Arabidopsis was more effective if the transgene was driven by the lignification-associated Arabidopsis cinnamate 4-hydroxylase promoter than by the constitutive 35S promoter (Meyer et al, 1998). We therefore decided to utilize the previously characterized lignification-associated bean phenylalanine ammonia-lyase PAL2 promoter, which is strongly expressed in the vascular tissue of transgenic tobacco (Leyva et al, 1992;Shufflebottom et al, 1993), to drive expression of COMT and CCOMT transgenes in alfalfa.…”
Section: Cell Type Specificity Of the Bean Pal2 Promoter In Transgenimentioning
confidence: 99%
“…To test whether SmF5H can rescue the syringyl lignindeficient phenotype of fah1-2, we transformed into the mutant a construct in which the SmF5H gene was under the control of the Arabidopsis C4H promoter, a strategy previously reported to efficiently target transgene expression to vascular tissue (6). Stem cell wall samples were prepared from the 17 independent fah1-2-pAtC4H::SmF5H T1 transgenic lines and were analyzed for lignin composition by using the DFRC method.…”
Section: Complementation Of Arabidopsis F5h-deficient Mutant By Smf5hmentioning
confidence: 99%
“…1) (3). C4H and C3ЈH are responsible for phenylpropanoid 4 and 3-hydroxylation (4, 5), respectively, whereas F5H catalyzes the 5-hydroxylation of coniferaldehyde and coniferyl alcohol, leading to the formation of syringyl lignin (6,7). Lignin monomer composition has been found to vary among major phyla of vascular plants (2).…”
mentioning
confidence: 99%